OPTIMASI PRODUKTIVITAS ORGANISASI MELALUI MANAJEMEN STRATEGIS SUMBER DAYA MANUSIA DI ERA DIGITAL - Faisal faisal (Jurnal Al Wadiah, 2023)
The digital era has changed the business landscape, giving rise to new challenges in optimizing organizational productivity. Strategic Human Resources Management (HRM) is the key in dealing with this dynamic. This research aims to analyze the implications of HRM on organizational productivity in the digital era and explore practical recommendations to improve it. This research uses a qualitative approach with secondary data analysis. This data includes the results of previous research as well as case studies of companies that have successfully optimized productivity through HRM in the digital era. The results of the analysis show that employee competency development, fair compensation programs, attention to welfare, use of technology, and continuous evaluation are key factors in increasing productivity. The implication of this research is the importance of strong HRM strategy integration in every aspect of the business.